Evaluation of the prenatal diagnostic value of non-invasive prenatal testing for the detection of rare fetal autosomal trisomies: a single center study of 83,842 cases - Yiming Chen; Xiaoxia Wu; Huawei Li; Yixuan Yin; Yanzhen Zhang (Scientific Reports)
Abstract To investigate the prenatal diagnostic value and pregnancy outcomes of rare autosomal trisomies (RATs) as indicated by non-invasive prenatal testing (NIPT), and to contribute to good childbearing. This was a retrospective and cross-sectional analysis of 83,842 pregnant women who received NIPT in our hospital. Amniotic fluid karyotype analysis and SNP-array chip detection were used to evaluate the prenatal diagnostic value and pregnancy outcomes of pregnant women at high-risk of RATs. In 83,842 pregnant women, 331 were identified to be at high-risk of RATs; the positive screening rate was 0.39% (331/83,842). Among the 331 women at high risk of RATs, 245 received invasive prenatal diagnosis, and the referral reasons for NIPT were advanced maternal age (≥ 35 years), serological borderline risk, and single serological marker median (MoM) abnormality, with the constituent ratios of 27.35% (67/245), 19.18% (47/245) and 17.55% (43/245), respectively. In these 245 pregnant women at high-risk of RATs, the most common screening-risk results were trisomy 7 (33.88%), trisomy 8 (13.47%), trisomy 20 (11.43%), trisomy 3 (7.35%), and trisomy 10 (6.12%); the rarest conditions were trisomy 6 (0.41%), trisomy 12 (0.82%), trisomy 14 (0.82%), and trisomy 4 (1.22%). Trisomy 1, 17 and 19 weren’t screened. The positive predictive value (PPV) for RATs in women at high-risk was 13.06%, and the PPVs for trisomy 9, 16, 15, 10 and 2 were 42.86%, 40.00%, 25.00%, 20.00%, and 16.67%, respectively. NIPT indicated that for pregnant women at high-risk of RATs, the PPVs for trisomy 9, 16, 15 and 10 were relatively high, while the PPV for other trisomies were low. With the exception of trisomy 9, 15, 16 and 10, most RATs were associated with good pregnancy outcomes. In clinical genetic counseling for RATs, the principle of individualized medicine should be reflected, and different prenatal diagnostic measures should be adopted for different RATs to advise pregnant women on whether to continue or terminate the pregnancy.